Pancasila Values Education In Learning History In Indonesia - Erisya Pebrianti Pratiwi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Multicultural education with Pancasila values aims to change schools, so that all students can learn about the knowledge, attitudes and skills needs to be applied in countries and worlds that have different races and cultures. Multicultural education with Pancasila values as a new discourse in Indonesia can be implemented not only through formal education, but can also be implemented in daily life in the community as well as in families (nonformal and informal education). In multicultural education, some dimensions need to be considered as well as facts that need to be put forward in connection with the outbreak of conflict in society that if not immediately addressed will be more protracted. Multicultural education can be implied in the world of education where there are seven ways in this article. In implementing Pancasila values with multicultural education in students in schools, as educators and teachers will encounter obstacles or challenges in their implementation. The innovation of historical learning is required in historical subjects in shaping the character of students.